Experience in Social Affective Applications: Methodologies and Case Study - André, Paul; Dix, Alan; schraefel, m.c.; White, Ryen W. (ACM SIGCHI Conference on Human Factors in Computing Systems (ALT.CHI 2010), April 10 - 15, 2010, Atlanta, GA, USA, 2010)
New forms of social affective applications are emerging, bringing with them challenges in design and evaluation. We report on one such application, conveying well-being for both personal and group benefit, and consider why existing methodologies may not be suitable, before explaining and analyzing our proposed approach. We discuss our experience of using and writing about the methodology, in order to invite discussion about its suitability in particular, as well as the more general need for methodologies to examine experience and affect in social, connected situations. As these fields continue to interact, we hope that these discussions serve to aid in studying and learning from these types of application.